Correction: Tailoring of optical properties of fluorescein using green synthesized gold nanoparticles. Issue 40 (9th October 2017) - John, Jisha; Thomas, Lincy; George, Nibu A.; Kurian, Achamma; George, Sajan D.
Abstract : Correction for 'Tailoring of optical properties of fluorescein using green synthesized gold nanoparticles' by Jisha John et al., Phys. Chem. Chem. Phys., 2015, 17, 15813–15821.